Subcortical Volume Changes in Schizophrenia and Bipolar Disorder: A Quantitative MRI Study - Demir, Mehmet; Findikli, Ebru; Tuncel, Deniz; Atay, Emre; Baykara, Murat; Acer, Niyazi; Doganer, Adem (Soc Chilena Anatomia, 2024)
Volume abnormalities in subcortical structures, including the hippocampus, amygdala, thalamus, caudate, putamen, and globus pallidus have been observed in schizophrenia (SZ) and bipolar disorder (BD), not all individuals with these disorders exhibit such changes. In addition, the specific patterns and severity of volume changes may vary between individuals and at different stages of the disease. The study aims to compare the volumes of these subcortical structures between healthy subjects and individuals diagnosed with SZ or BD. Volumetric measurements of lateral ventricle, globus palllidus, caudate, putamen, hippocampus, and amygdale were made by MRI in 52 healthy subjects (HS), 33 patients with SZ, and 46 patients with BD. Automatic segmentation methods were used to analyze the MR images with VolBrain and MRICloud. Hippocampus, amygdala and lateral ventricle increased in schizophrenia and bipolar disorder patients in comparison with control subjects using MRIcloud. Globus pallidus and caudate volume increased in patients with schizophrenia and bipolar disorder compared control subjects using Volbrain. We suggested that our results will contribute in schizophrenia and bipolar disorder patients that assessment of the sub-cortical progression, pathology, and anomalies of subcortical brain compositions. In patients with psychiatric disorders, VolBrain and MRICloud can detect subtle structural differences in the brain.
Cambios en el Volumen Subcortical en la Esquizofrenia y el Trastorno Bipolar: Un Estudio Cuantitativo de Resonancia Magnética
Keywords: MRI; Bipolar disorder; Schizophrenia; MRIcloud; Volbrain